Life without Fe–S clusters. Issue 5 (22nd December 2015) - Rocha, Agostinho G.; Dancis, Andrew
Summary: Fe–S clusters are critically important cofactors implicated in numerous cellular processes, including respiration, amino acid biosynthesis, cofactor biosynthesis, tRNA modification, DNA repair and regulation of gene expression. In the accompanying manuscript, Tanaka et al . show that reengineering of the isoprenoid biosynthetic pathway in E . coli (to bypass the usage of essential Fe–S cluster proteins by inserting the mevalonate pathway) can offset the indispensability of the Fe–S cluster biosynthetic systems. They show that the resulting Δisc Δsuf double mutants supplemented with mevalonate can grow slowly without detectable Fe–S cluster proteins. This result is astounding and raises interesting questions about what is essential and what is dispensable in the compendium of Fe–S cluster protein functions in this cell.